Alliances of leading biopharmaceutical companies as a strategic axis for the development of anti-COVID-19 vaccines - José Miguel Rodríguez Perón; Mario Miguel Rodríguez Izquierdo (Revista Cubana de Medicina Militar)
Alliances of leading biopharmaceutical companies as a strategic axis for the development of anti-COVID-19 vaccines